Development of E-Comic Learning Media Assisted by Video in Science Learning on Human Blood Circulation Material - Shinsya Arika Sukma; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2024)
The lack of innovation in learning media at SDN Lumbungmas 01 impacts student learning outcomes. This research is of the RnD (Research and Development) type, referring to the Borg and Gall model. The purpose of this study is to test the feasibility, practicality, and effectiveness of developing e-comic media assisted by video. The population used consists of 12 students from class VB on a small scale and 22 students from class VA on a large scale at SDN Lumbangmas 01, totaling 34 students. Data collection techniques include tests and non-tests. The test technique involves pretests and posttests, while non-test techniques involve interviews, observations, questionnaires, and documentation data. The feasibility scores given by media, material, and language expert validators show that the development of e-comic media meets the criteria for being highly feasible with scores of 90% (very feasible), 90% (very feasible), and 70% (feasible), respectively, resulting in an average of 83.3% (very feasible). The practicality of media development, assessed through questionnaires, indicates it is highly practical. Based on pretest and posttest results, the e-comic media development meets the criteria for effectiveness. This is evident from the effectiveness analyzed through the t-test and N-gain test. The t-test shows that Sig. < 0.05, meaning there is a significant difference between learning outcomes before and after treatment. The N-gain test shows high criteria, with 0.6182 on a small scale and 0.7173 on a large scale. Based on these results, it can be concluded that the development of e-comic media assisted by video is feasible, practical, and effective for use in learning for fifth-grade students at SDN Lumbungmas 01